The Correlation of Regional Economic Indicators to Poverty, Unemployment, and Economic Resilience in the Kadungsepur National Strategic Area - Rindirindi, Bagas (Dinasti International Journal of Education Management and Social Science, 2025)
This study analyzes the dynamics of poverty and unemployment in the Kedungsepur National Strategic Area (KSN) during the 2013–2023 period within the framework of regional economic resilience and development policy. A descriptive quantitative approach was employed using secondary data from Statistics Indonesia (BPS) and the Regional Development Planning Agency (Bappeda) of Central Java, covering six administrative areas: Semarang City, Salatiga City, and the Regencies of Semarang, Demak, Kendal, and Grobogan. The analysis was conducted through socio-economic trend calculations and Pearson correlation tests among regional economic indicators, including Regional Own-Source Revenue (PAD), the Human Development Index (HDI), Regional Minimum Wage (UMR), poverty rate, and open unemployment rate (TPT). The results indicate that the average poverty rate decreased from 10.65% in 2013 to 8.20% in 2023, while the unemployment rate decreased from 6.01% to 4.93%. However, Semarang Regency experienced a slight increase in unemployment (from 3.9% to 4.05%), indicating a jobless growth phenomenon. The correlation between HDI and poverty shows a very strong negative correlation (r = –0.976), implying that improved human quality significantly contributes to poverty reduction. Conversely, the positive correlation between minimum wage and unemployment (r = 0.795) suggests that wage increases without productivity improvements may reduce employment absorption. The findings emphasize that economic growth in Kedungsepur remains non-inclusive, being concentrated in urban and capital-intensive sectors. Therefore, a resilience-oriented development and Local Economic Development (LED) approach is required to promote economic diversification, enhance workforce skills, and ensure equitable distribution of development benefits. The study contributes to the formulation of regional development policies that are equitable, resilient, and sustainable.